Understanding Human Perception of Artificial Light at Night and Preferred Lighting Conditions in Parks and Protected Areas: A Pilot Study - CRUMP, Morgan; TAFF, Derrick B.; BEECO, Adam J.; WHITE, Jeremy; BUCKLEY, Stephanie; LAWSON, Steve; NEWMAN, Peter (Journal of Environmental Management and Tourism, 2025)
Naturally dark environments are increasingly threatened by artificial light at night (ALAN), even in parks and protected areas (PPAs). This study explores visitor preferences for lighting spectra and intensity in front-country, PPA-like settings to better understand how to balance human lighting needs with the protection of ecological and cultural resources. An onsite survey was conducted at a university arboretum in the United States (n = 167). Participants were asked to select preferred lighting conditions (color and intensity) using bollard fixtures with adjustable amber and white LEDs. Statistical analyses examined spectra and intensity preferences as well as demographic influences (gender, youth environment, nighttime recreation experience). Results indicate a significant preference for amber light (67%) over white light (33%). On average, participants preferred amber light at lower intensities (2.87 lux) compared to white light (5.18 lux). Prior nighttime recreation experience was associated with lower preferred light intensity and stronger selection of amber light. Participants from rural and suburban backgrounds were more likely to choose amber, while urban-raised participants showed no clear preference and tended toward higher intensities when selecting white light. This pilot study is one of the first to experimentally examine visitor lighting preferences in relation to both spectra and intensity in a PPA-like setting. Findings challenge assumptions based on industry standards, which often recommend higher light levels, and provide context-sensitive guidance for PPA lighting management. The sample consisted largely of university students, limiting age diversity and generalizability. Future research across broader populations and within actual PPAs is needed to validate results. Findings suggest that lower-intensity amber lighting can meet visitor needs while minimizing ecological impacts, offering managers evidence-based strategies for sustainable lighting design in PPAs. By aligning visitor preferences with conservation goals, PPA managers can protect naturally dark skies while maintaining visitor safety and experience, supporting the rise of noctourism - nighttime recreation and tourism that values darkness as a resource - and reinforcing the cultural and ecological significance of darkness as a shared resource.